2021
DOI: 10.1088/1361-6382/ac12e4
|View full text |Cite
|
Sign up to set email alerts
|

The shadow and photon sphere of the charged black hole in Rastall gravity

Abstract: Considering a charged black hole (BH) surrounded by a perfect fluid radiation field (PFRF) in Rastall gravity, we investigate this BH shadow and photon sphere on different spherical accretions backgrounds. The effect of the PFRF parameter/BH charge on the critical impact parameter is studied by investigating the light deflection near this BH. The luminosity of these BH shadows in different spherical accretions is obtained, respectively. It is found that the shadow of this BH with infalling spherical accretion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…In our previous work, we investigated the shadow and photon sphere of a charged BH with a perfect fluid radiation field (PFRF) surrounded by the static/infalling spherical accretion within the framework of the Rastall gravity. It is found that the shadow luminosity of this BH with infalling spherical accretion is dimmer than that of the static spherical accretion, but the photon sphere luminosity is brighter than the static one [29]. It is well known that the radiation received by our telescope comes not from the BHs themselves, but instead originates in the accretion disks which surround them.…”
Section: Introductionmentioning
confidence: 87%
“…In our previous work, we investigated the shadow and photon sphere of a charged BH with a perfect fluid radiation field (PFRF) surrounded by the static/infalling spherical accretion within the framework of the Rastall gravity. It is found that the shadow luminosity of this BH with infalling spherical accretion is dimmer than that of the static spherical accretion, but the photon sphere luminosity is brighter than the static one [29]. It is well known that the radiation received by our telescope comes not from the BHs themselves, but instead originates in the accretion disks which surround them.…”
Section: Introductionmentioning
confidence: 87%
“…Guo et al considered a charged BH surrounded by a perfect fluid radiation field within the framework of the Rastall gravity. They investigated the shadow and pho-ton sphere of this BH with the static/infalling spherical accretion background and obtained that the shadow luminosity of this BH with infalling spherical accretion is dimmer than that of the static spherical accretion, but the photon sphere luminosity is brighter than the static one [27]. Notably, they also showed that the luminosities of both the shadows and rings of the Hayward BH are affected by the accretion flow property and the BH magnetic charge [28].…”
Section: Introductionmentioning
confidence: 99%
“…The optical appearance of black holes in the context of Rastall gravity with different spherical accretions has been also studied in Ref. [35]. For further studies about the effect of the location and profile of accretion flow which surrounded the black hole space-times in alternative gravity theories see, [36]- [57].…”
Section: Introductionmentioning
confidence: 99%